Rationale and protocol of the Study Of diabetic Nephropathy with AtRasentan (SONAR) trial: A clinical trial design novel to diabetic nephropathy. Issue 6 (9th March 2018) - Heerspink, Hiddo J. L.; Andress, Dennis L.; Bakris, George; Brennan, John J.; Correa‐Rotter, Ricardo; Dey, Jyotirmoy; Hou, Fan Fan; Kitzman, Dalane W.; Kohan, Donald; Makino, Hirofumi; McMurray, John; Perkovic, Vlado; et al.
Abstract : Aims: Individuals with diabetes and chronic kidney disease (CKD) are at high risk for renal events. Recent trials of novel treatments have been negative, possibly because of variability in response to treatment of the target risk factor. Atrasentan is a selective endothelin A receptor antagonist that reduces urinary albumin‐to‐creatinine ratio (UACR), with a large variability between patients. We are assessing its effect on renal outcomes in the Study Of diabetic Nephropathy with AtRasentan (SONAR; NCT01858532) with an enrichment design (>30% lowering of albuminuria) to select patients most likely to benefit. Materials and Methods: SONAR is a randomized, double‐blind, placebo‐controlled trial with approximately 3500 participants who have stage 2–4 CKD and macroalbuminuria and are receiving a maximum tolerated dose of a renin‐angiotensin system inhibitor. Results: After 6 weeks of exposure to atrasentan 0.75 mg once daily (enrichment period), participants with ≥30% UACR decrease and no tolerability issues (responders) were randomly assigned to placebo or atrasentan 0.75 mg/day. The responder group will be used for primary efficacy and safety analyses. Approximately 1000 participants with <30% UACR reduction (non‐responders) were also randomized to placebo or atrasentan. The primary endpoint is a composite of a sustained doubling of serum creatinine or end‐stage renal disease. The original power calculation indicated that a total of 425 primary renal events in the responder group provides 90% power to detect a 27% reduction in relative risk (alpha level of .05). Conclusion: SONAR aims to determine whether atrasentan added to guideline‐recommended therapies safely reduces the risk of CKD progression and delays the onset of end‐stage renal disease in patients with type 2 diabetes and nephropathy. SONAR also aims to establish whether the enrichment of patients based on their initial "surrogate" response to atrasentan will deliver a trial design in accord with personalized treatment of diabetic kidney disease.